Association between specific language impairment and behavioral disorders among preschool children - Yudianita Kesuma; Rismarini Rismarini; Theodorus Theodorus; Mutiara Budi Azhar (Indonesian Pediatric Society, 2014)
BackgroundSpecific language impairment (SU) is the mostcommon developmental disorder in preschool children, causingserious impairmentE on behavioral development. To date, there havebeen few studies on SU and behavioral disorders in Palembang.ObjectiveTo assess for an association between SU and behavioraldisorders in preschool children in Palembang.MethodsSubjects in this cross-sectional study were childrenwho attended kindergarten. Their general characteristics,developmental history and physical examination results (includingweight and height) were recorded. We administered the SpecificLanguage Impairment checklist for language impairment and thePediatric Symptom Checklist 17 (PSC 17) for behavioral disorders.Data was analyzed by Chi-square test.ResultsWe studied 1,340 children from21 kinderg:irtens in Palembang.Prevalence of SU was 12.9%, consisting of expressive languageimpairment (10.2%), receptive impairment (0.5%) and mixed languageimpairment (2 .2%). The prevalence of behavioral disorders was15.1 %, consisting of internalization disorder (6.0%), externalizationdisorder (5.0%), attentive disorder (0.4%), and various combinationsof three disorders (3. 7%). A highly significant association was foundbetween SU and behavioral disorders (P=0.000; OR=2.082; 95%CI 1. 419-3 .053. Expressive language impairment was associated withexternalization and mixed behavioral disorders. Mixed languageimpairment was associated with internalization, attentive, and mixedbehavioral disorders. Howevei; receptive language disorder was notassociated with any behavioral disorders.ConclusionSU is significantly as sociated with behavioraldisorders. With regards to the individual SU types, expressivelanguage impairment is associated with externalization and mixedbehavioral disorders; mixed language impairment is associatedwith internalization, attentive and mixed behavioral disorders;but receptive language disorder is not associated with behavioraldisorders.